Informing policy with health labour market analysis to improve availability of family doctors in Tajikistan - Jamoliddin Abdullozoda; Salomudin Yusufi; Sulakshana Nandi; Parvina Makhmudova; Juana Paola Bustamante; Margrieta Langins; Alba Llop-Gironés; Ilker Dastan; Victor Olsavszky; Shukhrat Sultonov; Zebo Najmuddinova; Natasha Azzopardi-Muscat; et al. (Human Resources for Health)
Abstract Background Tajikistan has embarked on health reforms to orient the health system towards primary health care (PHC). The health labour market analysis (HLMA) was initiated by the Ministry of Health with the World Health Organization (WHO) on policy questions related to the PHC workforce team. This article presents the results with focus on family doctors as a critical part of the PHC team, providing lessons for strengthening family medicine and PHC in the European Region and central Asia. Methods The HLMA framework was used to guide the analysis. The data for analysis were provided by the Ministry of Health and Social Protection of the Population of the Republic of Tajikistan. Descriptive means were used to analyse the data. A Technical Working Group guided the process. Results There has been an increase in the number of health workers in the country over the last 7 years. However, there is a huge shortage of family doctors when compared with norms, with decreasing family doctor densities over the last 7 years. Family doctors have the highest vacancy rates among specialists and also constitute the highest proportion of specialists who migrate. There is inequitable distribution of doctors across the regions. Overall number of enrolments and graduates in family medicine are declining. Although salaries in PHC are higher than in hospitals, the overall health workforce salaries are lower than the national average. While there have been efforts to retain and attract doctors to PHC in rural and remote regions, challenges exist. The attraction of doctors to narrow specialties may be leading to undermining PHC and family medicine. While the optimal skill-mix and availability of nurses provide an opportunity to strengthen multi-disciplinary teams at the PHC level, shortages and unequal distribution of doctors are affecting health services coverage and health indicators. Conclusions Application of the HLMA framework has helped identify the bottlenecks in the health labour market flows and the possible explanations for them. The policy considerations emerging out of the HLMA have contributed to improving evidence-based planning for retention and recruitment of the PHC workforce, improvements in medical and nursing education, and higher investments in the PHC workforce and particularly in family doctors. Implementation of the Action Plan will require political commitment, financial resources, strong inter-sectoral collaboration, stakeholder management, and cross-country learning of best practices. Through this process, Tajikistan has shown the way forward in implementing the Central Roadmap for health and well-being in Central Asia and the Framework for Action on the Health and Care Workforce in the WHO European Region.